Simple and novel technique to confirm complete mitral isthmus block. (29th August 2018) - Takigawa, Masateru; Takahashi, Atsushi; Tanaka, Yasuaki; Martin, Claire A.; Nakashima, Emiko; Yamao, Kazuya; Sagawa, Yuichiro; Kuwahara, Taishi; Okubo, Kenji; Takahashi, Yoshihide; Watari, Yuji; Nakajima, Jun; et al.
Abstract: Background: Differential pacing technique to confirm mitral isthmus (MI) block is sometimes challenging due to destroyed tissues after extensive ablation. The purpose of this study is to set an endpoint of MI ablation using conduction time around the mitral annulus (MA). Methods: Forty‐five consecutive patients with persistent atrial fibrillation who received MI linear ablation were included. The geometry and activation times of the left atrium around the MA were collected using a multipolar catheter before ablation. During coronary sinus (CS) pacing, the time between the stimulus and the wave‐front collision at the opposite side of the MA (defined as T/2 ) was calculated, and the doubled value was defined as the estimated perimitral conduction time ( E‐PMCT ). The endpoint for complete MI block was when the stimulus (at distal CS) minus the maximal delayed potential ( St−MDP ) on the MI interval reached the E‐PMCT . Results: St−MDP reached E‐PMCT during MI ablation in 44/45 patients. Among these 44 patients, differential pacing revealed bidirectional block in 39/44 (88.6%), whereas in 5/44 (11.4%), the differential pacing was not possible because of the loss of capture of local potentials due to extensive applications around the linear line. In one patient, the St−MDP did not reach E‐PMCT ( E‐PMCT : 148 ms, St−MDP :130 ms) and differential pacing revealed no MI block. E‐PMCT values (median 176 ms) correlated strongly with St−MDP (median 185 ms, P < 0.0001, R = 0.98). Conclusions: Although E‐PMCT differs between individuals, the value is significantly correlated with the St−MDP . This technique may be useful in providing an individual endpoint of MI ablation as an alternative to differential pacing.